Psychological Well-being in Young University Students and the Perception of Affection Received from Grandparents - Pires, Heldemerina Samutelela; Mourão Lança, Mariana; Courelas Freire, Maria (Advances in Social Sciences Research Journal, 2026)
Psychological well-being is a central variable in positive psychological functioning, influencing self-acceptance, positive relationships with others, personal growth, life goals and autonomy. A positive relationship between grandparents and grandchildren can be a variable associated with the psychological well-being of both parties. The aim of this study was therefore to explore the relationship between the psychological well-being of young university students and the perception of affection received from their grandparents. 240 young university students of both genders aged between 18 and 25 took part in the study. The Scale of Affections between Grandparents and Grandchildren and the Scale for Measuring the Manifestation of Psychological Well-being were used. The results obtained show that there is a relationship between the psychological well-being of young university students and the perception of affections, particularly with regard to the “Love and Esteem” sub-scale.